2010
DOI: 10.1063/1.3464161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular χ(2) gratings via electron-beam lithography

Abstract: We show that the nonlinear optical activity of an organic molecule may be quenched by electron irradiation. Exploiting this effect, we inscribe periodic ͑2͒ patterns in the molecular films by means of a scanning electron microscope. The second harmonic diffraction efficiency of the resulting ͑2͒ gratings is measured. The relative intensity of the diffraction orders observed agrees with the expectations for a sheet of nonlinear dipoles with a periodic modulation. No linear diffraction is seen. The present metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It has been demonstrated with 6 ns frequency doubled mode‐locked Nd:YAG lasers forming an interference pattern, and with 100 mW from a CW krypton laser at 530.9 nm . Electron‐beam lithography is central in nanotechnology because of the level of control that it offers, for total or partial desorption of several types of organic films . Controlling the temperature and electron kinetic energy allows for partially damaging the molecular composition or for inducing reactions selectively; however, with these techniques, one usually has to move the sample in order to image the recorded region.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated with 6 ns frequency doubled mode‐locked Nd:YAG lasers forming an interference pattern, and with 100 mW from a CW krypton laser at 530.9 nm . Electron‐beam lithography is central in nanotechnology because of the level of control that it offers, for total or partial desorption of several types of organic films . Controlling the temperature and electron kinetic energy allows for partially damaging the molecular composition or for inducing reactions selectively; however, with these techniques, one usually has to move the sample in order to image the recorded region.…”
Section: Introductionmentioning
confidence: 99%
“…Equivalently, it can be shown that the position of the m order of diffracted second harmonic is given by: sinγm=sinθi+mtrue(λ/δtrue),with m=0,±1,±2,. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the nonlinear material is only covering the surface of the resonator it is, in principle, possible to achieve a periodic grating with the correct pitch. Recently, it was shown that the nonlinearity of molecular layers deposited on a flat surface could be quenched at will using an electron beam gun [70]. Exploiting this effect, periodic χ (2) patterns were inscribed on flat molecular films by means of a scanning electron microscope.…”
Section: Phase Matching and Quasi-phase Matching Of Wgmsmentioning
confidence: 99%